2016
DOI: 10.1128/jvi.01492-16
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Essential Genes in the Salmonella Phage SPN3US Reveals Novel Insights into Giant Phage Head Structure and Assembly

Abstract: Giant tailed bacterial viruses, or phages, such as Pseudomonas aeruginosa phage ϕKZ, have long genomes packaged into large, atypical virions. Many aspects of ϕKZ and related phage biology are poorly understood, mostly due to the fact that the functions of the majority of their proteins are unknown. We hypothesized that the Salmonella enterica phage SPN3US could be a useful model phage to address this gap in knowledge. The 240-kb SPN3US genome shares a core set of 91 genes with ϕKZ and related phages, ∼61 of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 57 publications
3
56
1
Order By: Relevance
“…This problem is exacerbated in "giant" or "jumbo" phages with long double-stranded DNA (dsDNA) genomes (Ͼ200 kb) (1,2), such as that of Pseudomonas aeruginosa phage KZ (280 kb), whose genome was the first giant phage genome to be published (3). Recent studies have demonstrated that phages related to KZ infect a range of clinically and agriculturally important gammaproteobacteria, including Salmonella enterica (e.g., SPN3US), Cronobacter sakazakii (e.g., CR5), and Erwinia amylovora (e.g., PhiEaH2) (3)(4)(5)(6)(7)(8)(9)(10). These giant phages are of interest for biocontrol purposes (e.g., phage therapy) and the fact that they have many unusual characteristics compared to other phage types.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This problem is exacerbated in "giant" or "jumbo" phages with long double-stranded DNA (dsDNA) genomes (Ͼ200 kb) (1,2), such as that of Pseudomonas aeruginosa phage KZ (280 kb), whose genome was the first giant phage genome to be published (3). Recent studies have demonstrated that phages related to KZ infect a range of clinically and agriculturally important gammaproteobacteria, including Salmonella enterica (e.g., SPN3US), Cronobacter sakazakii (e.g., CR5), and Erwinia amylovora (e.g., PhiEaH2) (3)(4)(5)(6)(7)(8)(9)(10). These giant phages are of interest for biocontrol purposes (e.g., phage therapy) and the fact that they have many unusual characteristics compared to other phage types.…”
mentioning
confidence: 99%
“…In KZ, the E proteins form a large (15 to 20 MDa) proteinaceous structure-the inner body (IB)-wrapped within the packaged DNA (16). We recently determined that the SPN3US head contains 50 different proteins, the most abundant being the major capsid protein (MCP), which forms the outer shell, and the E proteins gp53 and gp54 (10,15). Giant phage E proteins are assumed to enter the host cell with the phage genome because the KZ IB disappears upon ejection of the genome (17).…”
mentioning
confidence: 99%
“…Similarly, robust lung fibrosis is observed as early as 16–18 weeks postirradiation (24, 52), which is likely due to the use of younger mice (6–8 weeks old) instead of slightly older mice (10–12 weeks old) in the thorax irradiations. Importantly, thoracic exposure models provide useful and much needed information on partial exposure scenarios where lung only is exposed or when radionuclides are inhaled.…”
Section: Discussionmentioning
confidence: 98%
“…Bronchoalveolar lavage fluid (BALF) cytokine concentrations were determined, as previously described (24), using the Mouse Cytokine 20-Plex Panel (Invitrogen ™ , Carlsbad, CA), according to the manufacturer’s protocol. This multiplex panel permits simultaneous quantification of multiple cytokines in solution by capturing them onto antibody-coated spectrally distinct fluorescent microspheres and measuring fluorescence intensity using the BioPlex 200 (Bio-Rad ® Laboratories Inc., Hercules, CA) system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation